Breaking the constraint on the number of cervical vertebrae in mammals: On homeotic transformations in lorises and pottos. Issue 6 (31st October 2022) - Galis, Frietson; Van Dooren, Tom J. M.; van der Geer, Alexandra A. E.
Abstract: Mammals almost always have seven cervical vertebrae. The strong evolutionary constraint on changes in this number has been broken in sloths and manatees. We have proposed that the extremely low activity and metabolic rates of these species relax the stabilizing selection against changes in the cervical count. Our hypothesis is that strong stabilizing selection in other mammals is largely indirect and due to associated pleiotropic effects, including juvenile cancers. Additional direct selection can occur due to biomechanical problems (thoracic outlet syndrome). Low metabolic and activity rates are thought to diminish these direct and indirect effects. To test this hypothesis within the primates, we have compared the number of cervical vertebrae of three lorisid species with particularly low activity and metabolic rates with those of more active primate species, including with their phylogenetically closest active relatives, the galagids (bushbabies). In support of our hypothesis, we found that 37.6% of the lorisid specimens had an abnormal cervical count, which is a higher percentage than in the other nine primate families, in which the incidence varied from zero to 2.2%. We conclude that our data support the importance of internal selection in constraining evolvability and of a relaxed stabilizing selection for increasing evolvability. Additionally, we discuss that there is no support for a role of the muscularized diaphragm in the evolutionary constraint. Abstract : The number of neck vertebrae in mammals is virtually always seven. Sloths and manatees are famous exceptions to this rule. This is hypothesized to be due to relaxed stabilizing selection against changes, made possible by their extremely low metabolic and activity rates. Here we present further support for this hypothesis, as we find that lorisid primates, also known for their extreme slowness, provide another example of relaxation of this strong evolutionary constraint.